CONTRASTIVE ANALYSIS OF PHRASEOLOGISMS IN ENGLISH AND UZBEK MEDIA TEXTS - Shahrizoda Nuriddinova Akmal qizi (TADQIQOTLAR, 2025)
Abstract: Phraseologisms represent one of the most expressive layers of language and play a particularly significant role in media discourse. This article presents a contrastive analysis of phraseological units used in English and Uzbek media texts, focusing on their lexical-semantic characteristics, structural patterns, pragmatic functions, and cultural specificity. Media discourse relies heavily on figurative language to influence public opinion, convey evaluation, and ensure emotional engagement, making phraseologisms a powerful linguistic tool. The study is based on materials collected from newspapers, online news portals, and analytical media articles in both languages. Descriptive, comparative, and contextual analysis methods are applied. The findings reveal that while English and Uzbek media phraseologisms share universal cognitive mechanisms such as metaphor and metonymy, they differ considerably in structural organization, stylistic preference, and cultural orientation. The article highlights the importance of phraseological competence for translation, media literacy, and intercultural communication.